Das vollständige zentral-projektive Zusammenhangsobjekt und das Torsion-Krümmungsobjekt der Mannigfaltigkeiten von Zentralkopunktoren - Bliznikas, V. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Близникас. О взаимном расположении простых гауссовых чисел на кручения-кривизны пространства центральных копункторовV. Bliznikas. Centrinių kopunktorių erdvės centroprojektyvinio sąryšio pilnas objektas ir sukimosi — kreivumo objektas